Variety age and maize yield in Zambia: climate-smart benefits of varietal turnover under production stress - Mulungu, Kelvin; Cairns, Jill; Jaleta, Moti (CIMMYT, 2025)
Agricultural productivity growth in sub-Saharan Africa has stagnated despite sustained investments in crop improvement research, with maize yields showing concerning signs of decline since the 2000s. This study examines whether slow varietal turnover (the replacement of older varieties with newer improved varieties) constrains productivity growth in Zambian maize systems. Using nationally representative panel data spanning 2012-2019 and covering 11,065 plot-level observations from 8,369 households, we estimate the relationship between variety age and yield while controlling for household and plot characteristics through fixed and random effects models. First, we find that female-headed households use varieties 2-3 years older on average, pointing to equity concerns in variety access. Our analysis reveals that each additional year of variety age reduces maize yields by 8.5-20 kg/ha depending on model specification. These effects are substantially larger than previously documented in African contexts. Our results are robust to different causal identification strategies. The effects are highly heterogeneous across production conditions, with newer varieties providing greatest yield advantages under drought stress, late planting, low fertilizer application, and high temperatures, demonstrating successful incorporation of climate-smart traits in recent breeding efforts. However, newer varieties do not outperform older ones under pest and disease pressure, highlighting gaps in biotic stress tolerance. Economic analysis reveals benefit-cost ratios of 3.5-8.3 for adopting varieties one year newer than average age (13 years), indicating strong financial incentives for variety turnover. Our findings suggest that accelerating varietal turnover represents an important but underutilized pathway for agricultural productivity growth and climate adaptation in sub-Saharan Africa.